The transaction costs theory in international business research: a bibliometric study over three decades - Ferreira, Manuel Portugal (2021)
Transaction costs theory (TCT) has long been an important conceptual lens for examining International Business (IB) phenomena and perhaps especially relevant for the study of multinational corporations, entry mode choices and location selection. In this paper we examine the extent to which TCT been used and has impacted IB research. Methodologically, we conduct a bibliometric study of the articles published on nine top journals for publishing IB-related research. We use Jean-Franc¸ois Hennart’s research as the key marker for TCT in IB research given that Hennart’s work has been a hallmark in the discipline. On a sample of 377 articles published between 1982 and 2010, and using the works rather than the authors as the unit of analysis, we analyze citations, co-citations and a spatial visualization of the intellectual research themes delved into. Our analyses provide insights on the influence of Hennart but more broadly of TCT on IB research over the past three decades. We conclude that the TCT has a pervasive influence on a large array of IB research and that Hennart’s work is boundary-spanning, connecting several research themes.